Effects of neural tension in the sciatic nerve stiffness, in healthy people and people with low back related leg pain - Neto, Tiago Gonçalves (2020)
Neurodynamics techniques, such as neural tension maneuvers, are often used by health professionals to assess the peripheral nerves properties. They are also used in the rehabilitation of several lower body quadrant disorders (i.e. as in low back related leg pain – LBRLP), or as a training method in healthy individuals. Nevertheless, there is insufficient evidence of the neurodynamics effects, mainly neural tension, when applied to the lower body quadrant. This thesis aimed to determine the immediate effects of neural tension in the sciatic nerve stiffness, estimated by shear wave elastography, in both healthy people and people with LBRLP. Three studies were conducted to meet with this purpose: 1) a systematic review, with meta-analysis, which revealed evidence favoring the use of neurodynamics techniques for pain relief and disability improvement in people with low back pain, and for flexibility improvements in healthy people; 2) a study that showed no significant effects of neural tension in a slump position in reducing the sciatic nerve stiffness of healthy people; and 3) a study which determined that people with LBRLP present greater sciatic nerve stiffness in the affected limb compared to the unaffected limb, and to healthy controls; and that neural tension immediatly reduced the sciatic nerve stiffness of the affected limb. This thesis provides evidence of the clinical and mechanical effects of neurodynamics techniques, mainly neural stiffness. The effect of neural tension in reducing the sciatic stiffness in people with LBRLP seems to be related with changes in the nerve mechanical properties, however future research should confirm this finding while also determining the longterm effects of neurodynamics techniques.